STRATEGI PENCEGAHAN PERNIKAHAN USIA DINI MELALUI PENERAPAN PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) DI SMK NEGERI 1 BULUKUMBA - Andi Marlah Susyanti; Halim Halim (Politeknik STIA LAN Makassar, 2020)
The number of early marriages (15 years) is recorded highest in South Sulawesi. The figure reached 6.7% compared to the national figure of only 2.46%. The consequences of early marriage include the loss of children's rights such as education and being protected from exploitation, as well as the emergence of health problems. The purpose of this research is to describe the strategy of preventing early marriage through PIK-R at SMK Negeri 1 Bulukumba. The method used is qualitative method with case study design. Data obtained through structured interviews and document review. The informants in this study were 14 people, namely principals and teachers of SMK Negeri 1 Bulukumba (4 people), parents of students (5 people) and students (5 people). The data were analyzed with thematic analysis. The results showed that PIK-R has been implemented in SMK Negeri 1 Bulukumba through three strategies, namely child empowerment in school, family empowerment through parental supervision and emphasis on social factors that are at risk at early marriage. In its application this second strategy has not been optimal. The third strategy is to increase students' knowledge through formal education whose application has not been implemented, although students consider that knowledge related to early marriage is very important. This study recommends empowering the role of families, creating a local content curriculum related to reproductive health and prevention of early marriage, as well as follow-up research involving students who have not been involved in PIK-R activities.